PENGEMBANGAN KURIKULUM BERBASIS STEM UNTUK MENINGKATKAN KOMPETENSI SISWA DI ERA DIGITAL: TINJAUAN SYSTEMATIC LITERATURE REVIEW - Mustofiyah, Lilik; Fitri Puji Rahmawati; Anik Ghufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Through a systematic literature review, this study aimed to investigate STEM-based curriculum development strategies, identify key challenges in their implementation, and assess the impact of STEM-based curriculum implementation on students' capabilities in the digital era. We used a systematic literature review approach to identify, analyze, and synthesize findings from relevant studies. This research offers novelty by focusing on developing country contexts and using a comprehensive SLR approach. The results demonstrated several ways to implement STEM-based curriculum development strategies, including: 1) interdisciplinary integration. 2) project- and problem-based learning; 3) student-centered learning; 4) utilization of digital technology-based learning media; and 5) development of 21st-century competencies. The 21st century requires critical thinking, creativity, collaboration, and communication skills, all of which STEM education can enhance. However, there are various challenges in its implementation, especially in developing countries, including limited resources, infrastructure, and teacher training. This research pinpoints effective strategies to surmount these challenges, including enhancing teacher training, building infrastructure, and incorporating technology into the learning process. The research pinpoints strategies that effectively address these challenges, including enhancing teacher training, developing infrastructure, and incorporating technology into learning. The research is novel because it focuses on developing country contexts and uses a comprehensive SLR approach. The findings provide practical recommendations for educators and policymakers in implementing effective STEM curricula, as well as contributions to the academic literature in STEM education. Therefore, we anticipate that this research will contribute to the advancement of inclusive and high-quality education in the digital era.